Spatial Analysis of Health and Physical Parameters of the Mangrove Forest at Taman Hutan Raya Ngurah Rai, Bali Using Sentinel-2A - Muhammad Dimyati; Astridia Putri Nurhaliza; Astrid Damayanti (Indonesian Journal of Geography, 2022)
Mangrove forest is a very valuable forest, but despite its benefits mangrove forest continue to be degraded due to human activities. The purpose of this study was to map the distribution and to analyze mangrove forests’ health based on the NDVI vegetation index value and environmental quality. Distribution of mangrove forest health was obtained through the processing of sentinel 2-A satellite imagery in 2020 and field measurements. The environmental quality of the mangrove forest was obtained by processing the physical parameters which are water temperature, water salinity, water pH, and substrate texture using the Ordinary Kriging method. The health of the mangrove forest of Taman Hutan Raya Ngurah Rai is dominated by healthy category mangroves. The health of the mangrove forest worsens when closer to the shore and riverbanks. Mangrove vegetation with good conditions tends to have optimal environmental quality conditions and vice versa.